The Adaptive Helix Model: A Proposed Framework for Sustainable Innovation Value - Alnouman, Saleh (Global journal of Business and Integral Security, 2025)
Innovation zones and ecosystems (IZEs) are increasingly crucial for national development, economic support, and resource sustainability. However, many fail to meet expectations for reasons related to the structure and composition of the ecosystems model implemented or how these models are implemented. Existing helix models: Triple, Quadruple, Quintuple, and N-Tuple helix provide applicable conceptual models, but they are rigid and fragmented for dynamic and decentralized IZEs. This article presents the Adaptive Helix Model, a transformation-driven and holistic framework designed to ensure smooth and flexible implementation applicable to various types of IZEs. The model is structured around eight interconnected helices and components implemented by IZEs owners. This study demonstrates how the Adaptive Helix Model overcomes the gaps in existing helix models and the challenges facing IZEs. It also provides practical guidance for applying the model across diverse IZEs, aiming to enhance resilience and sustainable value creation. Keywords: Innovation zones and ecosystems, Helix models, Transformation, Adaptive systems.